I need a little bit of help here.

x(x-1)+(x-1)(x+2)
_____________
(x-2)(x+1)

How do you simplify that? Do you look for common factors? Or is it something else?

2 answers

[ x ( x - 1 ) + ( x -1 ) ( x + 2 ) ] / [ ( x - 2 ) ( x + 1 ) ] =

( x - 1 ) [ x + ( x + 2 ) ] / [ ( x - 2 ) ( x + 1 ) ] =

( x - 1 ) ( x + x + 2 ) / [ ( x - 2 ) ( x + 1 ) ] =

( x - 1 ) ( 2 x + 2 ) / [ ( x - 2 ) ( x + 1 ) ] =

( x - 1 ) ∙ 2 ( x + 1 ) / [ ( x - 2 ) ( x + 1 ) ] =

2 ( x - 1 ) / ( x - 2 )
Thank you!
Similar Questions
    1. answers icon 2 answers
  1. Rio Grande River - forms most of Texas’s _______boundaryRed River - Acts as part of the boundary between ____________ &
    1. answers icon 3 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions